Glycine Receptor-mediated Synaptic Transmission Regulates the Maturation of Ganglion cell Synaptic Connectivity - Xu, Hong-ping (2008)
It is well documented that neuronal activity is required for the developmental segregation of retinal ganglion cell (RGC) synaptic connectivity with ON and OFF bipolar cells in mammalian retina. Our recent study showed that light deprivation preferentially blocked the developmental RGC dendritic redistribution from the center to sublamina a of the IPL. To determine whether OFF signals in the visual stimulation are required for OFF RGC dendritic development, the light evoked responses and dendritic stratification patterns of RGCs in Spastic mutant mice, in which the OFF signal transmission in the rod pathway is largely blocked due to a reduction of glycine receptor (GlyR) expression, were quantitatively studied at different ages and rearing conditions. The dendritic distribution in the IPL of these mice was indistinguishable from wild type controls at the age of P12. However, the adult Spastic mutants had altered RGC light evoked synaptic inputs from ON and OFF pathways, which could not be mimicked by pharmacologically blocking of glycinergic synaptic transmission on age-matched wild type animals. Spastic mutation also blocked the developmental redistribution of RGC dendrites from the center to the sublamina a of the IPL, which mimicked the effects induced by light deprivation on wild type animals. Moreover, light deprivation of the Spastic mutants had no additional impacts on the RGC dendritic distribution and light response patterns. We interpret these results as that visual stimulation regulates the maturation of RGC synaptic activity and connectivity primarily through GlyR-mediated synaptic transmission.